1994
DOI: 10.1136/bmj.309.6957.765
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of headache and migraine in schoolchildren

Abstract: Objectives-To determine the prevalence rates of the various causes of severe headache in schoolchildren, with special emphasis on migraine and its impact on school attendance.Design-Population based study in two stages, comprising an initial screening questionnaire followed by clinical interviews and examination of children with symptoms and a control group of asymptomatic children matched for age and sex.Setting-67 primary and secondary schools in the city ofAberdeen.Subjects-2165 children, representing a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
530
12
31

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 693 publications
(613 citation statements)
references
References 14 publications
(12 reference statements)
40
530
12
31
Order By: Relevance
“…The prevalence of CDH in the adult population varies between 1.5% and 7% [9,10]; in children and adolescents it ranges from 0.2% to 0.9% [11,12]. In our study performed in juvenile subjects we observed 5.93% of the patients with primary headaches suffered from CDH: this higher percentage is due to the fact that subjects presenting to a tertiary care centre have more serious and disabling headache forms [13].…”
Section: Discussionmentioning
confidence: 45%
“…The prevalence of CDH in the adult population varies between 1.5% and 7% [9,10]; in children and adolescents it ranges from 0.2% to 0.9% [11,12]. In our study performed in juvenile subjects we observed 5.93% of the patients with primary headaches suffered from CDH: this higher percentage is due to the fact that subjects presenting to a tertiary care centre have more serious and disabling headache forms [13].…”
Section: Discussionmentioning
confidence: 45%
“…Population-based studies reported that the prevalence of migraine in childhood and adolescence ranges from 3% to 14% [1][2][3][4][5][6]. From the time of Wolff's early portrait of the childhood personality characteristics of migraine patients, the research began to explore the association of headache first with broad personality traits and then with distinct psychiatric symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These proportions dramatically increase during adolescence and may reach the 90% of the adolescent population [1,5,6]. About 15% of school age children suffer from recurrent headache, either tension-type headache or migraine, once a week or more [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These proportions dramatically increase during adolescence and may reach the 90% of the adolescent population [1,5,6]. About 15% of school age children suffer from recurrent headache, either tension-type headache or migraine, once a week or more [7][8][9].The frequency, intensity and quality of headaches have been associated with complex interactions between biological, psychological and socio/environmental factors [10][11][12][13]. Psychosocial mechanisms may be relevant in the etiology and pathogenesis of primary headaches and include social and economic status, resilience, housing conditions, family conditions, life events, school conditions and performance, leisure time activities, quality of life, situational factors, coping responses, psychiatric and somatic comorbidity, and behavioral problems [14].…”
mentioning
confidence: 99%